1991
DOI: 10.2307/1131005
|View full text |Cite
|
Sign up to set email alerts
|

Linking Extreme Marital Discord, Child Rearing, and Child Behavior Problems: Evidence from Battered Women

Abstract: Relations between marital discord, parental behavior, and child behavior were investigated in a sample of 37 battered women and 37 comparison mothers and their children, aged 2-8 years. It was hypothesized that violent fathers would be more irritable but less involved, battered women more stressed and inconsistent in discipline, and both parents would reportedly use fewer positive and more negative child-rearing responses than comparison families. Based on maternal self-reports and mother-child observations, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
117
0
10

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(135 citation statements)
references
References 0 publications
8
117
0
10
Order By: Relevance
“…In contexts of IPV against mothers, their children see, hear, and are involved in these episodes of violence [3]. Children may not always observe the violence directly (since, in many instances, the abuse is manifested as psychological and controlling behavior by the perpetrator), but they are still aware of the abuse that is taking place [2,4].…”
Section: Violence Experienced By Children In the Context Of Ipvmentioning
confidence: 99%
“…In contexts of IPV against mothers, their children see, hear, and are involved in these episodes of violence [3]. Children may not always observe the violence directly (since, in many instances, the abuse is manifested as psychological and controlling behavior by the perpetrator), but they are still aware of the abuse that is taking place [2,4].…”
Section: Violence Experienced By Children In the Context Of Ipvmentioning
confidence: 99%
“…Children exposed to IPV are more likely to experience harsh parenting, such as corporal punishment and verbal aggression (Holden & Ritchie, 1991; Levendosky, Lynch, & Graham-Bermann, 2000; Simmons et al, 2010), as well as more severe forms of harsh parenting and maltreatment that lead to involvement with child protective services (CPS; Appel & Holden, 1998; Colletti et al, 2008; Hartley, 2002; Nelson & Gold, 2012; Streisand, Braniecki, Tercyak, & Kazak, 2001). Both forms of violence increase children’s risk for clinically significant disruptive behavior (Evans, Davies, & DiLillo, 2008; Ferguson, 2013; Wolfe, Crooks, Lee, McIntyre-Smith, & Jaffe, 2003).…”
mentioning
confidence: 99%
“…One explanation for the substantial overlap between IPV and harsh parenting is a spillover mechanism, whereby conflictual behavior between parents spills over into their behaviors toward their children, with an increase in parenting strain and harsh parenting practices (Graham-Bermann & Levendosky, 1998; Holden & Ritchie, 1991; Levendosky, Lynch, & Graham-Bermann, 2000; Simmons et al, 2010). Examples of spillover include a mother generalizing the negative affect experienced in her conflictual relationship with her partner to her relationship with her child, responding to her child in similarly harsh ways, a mother becoming too emotionally drained by her conflictual relationship with her partner and having too few personal resources to respond to her child in sensitive ways, or a mother developing psychological health problems that then compromise parenting (Graham-Bermann & Levendosky, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated associations between maternal IPV and family-level variables, such as parenting and increased internalizing and externalizing symptoms in children of IPV survivors (Levendosky & GrahamBermann, 2001;Owen, Thompson, & Kaslow, 2006). Specifically, parenting difficulties (i.e., lower levels of parental warmth, control, parenting effectiveness, and child centeredness; Holden & Ritchie, 1991) and increased levels of parenting stress (Levendosky & Graham-Bermann, 1998;Owen et al, 2006) have been reported among women with IPV histories.…”
Section: Ipv and Parenting Stressmentioning
confidence: 99%